Does the Era of Globalization Dictate a change in the Definition of Public Health? - Zaletel Kragelj Lijana; Eržen Ivan (Sciendo, 2024)
Globalization has a major impact on public health in all countries of the world. Unfortunately, there are attempts to treat global challenges in the field of public health separately from national ones, following the model of tropical medicine, where the focus of action was in fact primarily on the identification and control of tropical diseases. This was especially in the interest of countries that colonized certain areas in the tropical part of the world. Global health, which is to some extent the successor of tropical medicine, cannot be a separate entity. The lines between global health and public health are blurring. In essence, global health is just another aspect of public health, important both in terms of recognizing the situation and taking action to improve the situation. The problems are mostly no longer local or national, and, to a greater or lesser extent, already affect the entire population or threaten the health of future generations.